2022
DOI: 10.52888/0514-2515-2022-353-2-121-134
|View full text |Cite
|
Sign up to set email alerts
|

On the 40<sup>th</sup> anniversary of the discovery of Helicobacter pylori

Abstract: The review is dedicated to the analysis of the accumulated data on the study of Helicobacter pylori (H. pylori) since the detailed description of this bacterium as the main etiological factor of gastrointestinal diseases. The work shows the dual role of H. pylori both as a bacterial pathogen for humans and as a potential representative of the normal microbiome of the stomach. In most scientific publications, the attention of researchers is focused entirely on the consideration of the pathogenic properties of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…H. pylori is a bacterium that is often found in patients with chronic gastritis, peptic ulcer, and gastric cancer, as well as among the healthy population [19,20]. Over a 40-year period of study of this bacterium, it has been convincingly shown that in patients with DM, both of the first and second types, H. pylori is detected more frequently than in the general population [2,3,21,22]. The high incidence of H. pylori in patients with DM is accompanied by low efficacy of eradicate on therapy [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori is a bacterium that is often found in patients with chronic gastritis, peptic ulcer, and gastric cancer, as well as among the healthy population [19,20]. Over a 40-year period of study of this bacterium, it has been convincingly shown that in patients with DM, both of the first and second types, H. pylori is detected more frequently than in the general population [2,3,21,22]. The high incidence of H. pylori in patients with DM is accompanied by low efficacy of eradicate on therapy [10,11].…”
Section: Discussionmentioning
confidence: 99%